STUDENTS’ PERCEPTION OF DIGITAL STORYTELLING TO IMPROVE ENGLISH SPEAKING ABILITY - Septi Rosalina; Syafryadin Syafryadin; Ari Andre Rianyansa (Wiralodra English Journal, 2025)
This study set out to find out what the students’ perception using digital storytelling as a teaching medium to improve the English speaking ability of EFL students. In order to learn what students’ perception is about using digital media as a teaching medium to boost students' EFL English speaking ability, A quantitative descriptive design is used in this study. The study's participants are 30 EFL students—10 male and 20 female—who received English instruction at Universitas Islam Negeri Fatmawati Sukarno Bengkulu (UINFAS). They were selected using stratified random sampling. Furthermore, two male and five female English instructors from the Al-Ain district were specifically chosen to take part in the group interview. Both quantitative and qualitative analyses were performed on the data. Thematic analysis was used to analyze the qualitative data, while percentage, frequency, and mean scores were used to analyze the quantitative data. Ten Literature questions were identified from the interview results. According to the results, the majority of instructors supported the use of digital storytelling in the classroom since it improved the process of teaching and learning English. The findings indicate that the use of digital storytelling in EFL classrooms was well-received by the students.